Acceptability Of Flexible Learning Scheme Among Essu-Maydolong Students (Journal of Namibian Studies : History Politics Culture, 2023)
Flexible learning scheme has been used by the education institutions in order to continue student’s learning amidst the pandemic. For some institutions like ESSU-Maydolong, the implementation of flexible (especially those with offline modes) proves to be done for the first time since most are practicing face-to-face classes before the advent of the pandemic. Hence, a study was conducted to determine the acceptability of flexible learning scheme among the students utilizing a descriptive survey approach. Respondents of the study were students officially enrolled in 1st Semester AY 2020-2021 from different course programs and year levels. The revealed that the acceptability of flexible/offline learning scheme among ESSU-Maydolong students was “neutral.” Nonetheless it showed important details on each category as well as student suggestions to help improve the said learning scheme.